(untitled) (Research, Society and Development, 2023)
This study aimed to verify the perceptions of professionals residing in health regarding the process of territorialization, understood as a tool that enables the epidemiological analysis of territories linked to health units and their populations. This is an exploratory study, with a qualitative approach, in which 11 resident health professionals working in a municipality in Ceará participated, carried out between February and April 2023. The data were constructed from semi-structured individual interviews, addressing questions about the perception of informants about the concept, strengths and weaknesses related to the territorialization process. The data obtained from the informants were submitted to content analysis. The informants associated territorialization as a process that facilitates recognition and approximation with the places of action. In the axis of potentialities, qualification of care and knowledge about the presence of assistance devices available in the municipal health network were cited. In the axis of weaknesses, the COVID-19 pandemic and the resistance of some professionals to carry out territorialization were related. Thus, although territorialization is perceived as a facilitator of health work, the perceived weaknesses demand qualification strategies for this process.